2013
DOI: 10.1111/ijd.12050
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF‐κB in the pathogenesis of psoriasis elucidated by its staining in skin biopsy specimens

Abstract: The study has demonstrated that translocation of NF-κB in the epidermis and basal cells is responsible for two of the key pathological features of psoriasis, epidermal hyperplasia, and inflammation. We have postulated that translocation of NF-κB in lymphocytes, in psoriatic skin leads to NF-κB translocation in the epidermis and basal cells. NF-κB is therefore likely to be one of the key molecules in the pathogenesis of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…The TNF-α-driven CCL20 release is mediated by keratinocytes and dermal fibroblasts [45]. Upregulation of these proinflammatory cytokines by TNF-α is facilitated through the activation of Nf-κB [46] – a transcription factor that is constitutively activated in psoriatic epidermis [47]. Elevated levels of Nf-κB facilitate keratinocyte hyperproliferation by inhibiting the cell cycle regulator protein, phosphatase 6, via the upregulation of the microRNA miR-31 [47].…”
Section: Resultsmentioning
confidence: 99%
“…The TNF-α-driven CCL20 release is mediated by keratinocytes and dermal fibroblasts [45]. Upregulation of these proinflammatory cytokines by TNF-α is facilitated through the activation of Nf-κB [46] – a transcription factor that is constitutively activated in psoriatic epidermis [47]. Elevated levels of Nf-κB facilitate keratinocyte hyperproliferation by inhibiting the cell cycle regulator protein, phosphatase 6, via the upregulation of the microRNA miR-31 [47].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have confirmed the presence of NF-κB activity in psoriatic (skin) disease (65),[65],[66]. However, in a human study, elevated active p65 was not reduced to normal baseline levels by TNF blockade, suggesting that TNF-independent NF-κB activity is present in psoriatic pathology [67].…”
Section: Molecular Pathways In Psa Pathogenesismentioning
confidence: 99%
“…VEGFR-2 could participate in the inflammatory process through p38, ERK1/2 and AKT pathway, which were upstream of NF-kB pathway. Besides, the activation of NF-kB could induce the production of inflammatory vascular markers (9). The mechanism by which HK exhibited anti-psoriatic effects maybe like this: HK inhibited VEGFR-2 signal through inhibition of p38, ERK1/2 and AKT, then inhibited the activation of NF-kB and inflammatory vascular markers.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytoid dendritic cells (pDCs), infiltrating in psoriatic lesions, also exacerbated the Th17-mediated pathogenesis of psoriasis (7,8). Furthermore, NF-kB has been proved to be a crucial factor in the initiation of the inflammatory response of psoriasis (9). The classic form of NF-kB is the heterodimer of the p50 and p65 (RelA) subunits, which contains the transcriptional activation domain and sequestered in the cytoplasm as an inactive complex by the inhibitory proteins IkBs.…”
Section: Introductionmentioning
confidence: 99%